Non-suicidal self-injury disorder as a stand-alone diagnosis in a consecutive help-seeking sample of adolescents - Ghinea, Denisa; Edinger, Alexandra; Parzer, Peter; Koenig, Julian; Resch, Franz; Kaess, Michael (Journal of affective disorders, 2020)
Background: With inclusion of non-suicidal self-injury disorder (NSSID) in the DSM-5, empirical data are crucial to gather information regarding its clinical validity and relevance. Until now, research focused mostly on single diagnostic criteria of NSSID. The present study aimed to characterize NSSID with and without comorbid diagnoses in a large help-seeking adolescent sample, investigating the clinical validity and selectivity of NSSID within the theoretical framework of Robins and Guze. Methods: Interview and self-report data of n = 464 adolescents (mean age = 14.95 years, SD = 1.43, 89.17% female) with NSSID according to DSM-5 from a German outpatient clinic were analysed with descriptive statistics. Group differences were calculated with chi(2) tests or t-tests respectively. Stability of NSSID without comorbidity was investigated after 12 months. Results: Within a consecutive help-seeking sample, NSSID as a stand-alone diagnosis (without comorbidity) was rare (only 3.7%), associated with low illness severity and psychopathological distress, and prospectively rather unstable. Limitation: Selection bias due to the help-seeking population and female preponderance. Conclusion: Based on the theoretical framework applied, NSSI should be considered as an unspecific precursor for psychopathological development generally and suicide specifically but it may be of limited significance as a `pure and sole' diagnostic entity. Results add to existing claims to re-propose classification criteria to better picture the clinical group of affected adolescents.
Gesehen am 30.07.2020